Method for determining conductive corrosion-resistant conversion film forming liquid

By using transition metal oxide salt on the surface of magnesium alloy as an oxidant in the film forming liquid and doping transition metal ions into the crystal lattice of the phosphate, the problem that it is difficult to take into account both conductivity and corrosion resistance on the surface of magnesium alloy is achieved. The preparation of an efficient and universal conductive corrosion-resistant conversion film is achieved.

CN119465123APending Publication Date: 2025-02-18NORTHEASTERN UNIV CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411394873.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both conductivity and corrosion resistance on the surface of magnesium alloys, and traditional chromate conversion films have carcinogenicity and environmental protection problems.

Method used

By calculating the energy band of transition metal oxide, electrode reaction and standard potential of oxidant, the oxide salts of Mn, V, Mo are selected as the oxidant in the film forming liquid, and doping transition metal ions in the crystal lattice of the phosphate. To improve the conductive and corrosion resistance of the film layer.

Benefits of technology

It is achieved without reducing the corrosion resistance of the film layer, improving the conductive properties of the film layer, and reducing the trial and error costs in the test without reducing the corrosion resistance of the film layer. This method is suitable for all magnesium alloys and is universal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465123A_ABST
    Figure CN119465123A_ABST
Patent Text Reader

Abstract

The invention provides a method for determining a conductive corrosion-resistant conversion film forming liquid. Comprising the following steps: selecting potassium permanganate and ammonium metavanadate as oxidants in a film-forming solution according to an energy band of a transition metal oxide, an electrode reaction and standard potential of the oxidants, the acid-base property of a film-forming substance solution, environmental factors, a precipitation equilibrium phase diagram of the transition metal oxide and a precipitation equilibrium phase diagram of monohydrogen phosphate, namely film-forming cations Ca < 2 + > in a film-forming substance; and then determining a solution containing 0.20 mol / L to 0.24 mol / L of calcium nitrate, 0.20 mol / L to 0.24 mol / L of ammonium dihydrogen phosphate, 0.05 mol / L to 0.2 mol / L of potassium permanganate and 0.01 mol / L to 0.03 mol / L of ammonium metavanadate as a film forming solution. According to the method for determining the conductive corrosion-resistant conversion film forming liquid, the trial and error cost can be reduced, and the conductive corrosion-resistant magnesium alloy conversion film can be simply and efficiently prepared by utilizing the determined conductive corrosion-resistant conversion film forming liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy surface treatment, and in particular to a method for determining a conductive corrosion-resistant conversion film-forming liquid. Background Art

[0002] Magnesium alloys can be used in electronic products, military industry, optical instruments, aerospace and other fields due to their good specific strength, specific stiffness, electromagnetic shielding ratio and damping and shock absorption performance. However, magnesium alloys have poor corrosion resistance, and surface treatment of magnesium alloys is an effective means to improve their corrosion resistance. Chemical conversion coatings have become an important means of surface protection due to their green environmental protection, simple operation and good corrosion resistance. In many aerospace and 3C electronic fields, the coating contact interface needs to be conductive, which requires the coating to have a very low contact resistance and at the same time have good corrosion resistance to protect the magnesium alloy from corrosion.

[0003] In magnesium alloy coating technology, chemical plating can meet the conductivity of the film layer, but due to the huge risk of galvanic corrosion, the magnesium alloy is accelerated to corrode, which limits its use. Although the traditional chromate conversion film can meet specific conductivity and corrosion resistance requirements, it is restricted due to its carcinogenicity and environmental problems. Therefore, it is of great significance to develop an environmentally friendly conductive and corrosion-resistant conversion film.

[0004] The problem with chromium-free conversion coatings is that it is difficult to balance electrical conductivity and corrosion resistance. Studies have shown that the introduction of transition metal oxides can improve the electrical conductivity of magnesium alloys, but the essential reason for the conductivity has not been pointed out, nor is there any theoretical guidance for designing solutions. At the same time, most of the film layers are at the nanoscale, which makes it difficult to improve corrosion resistance.

[0005] Some people have also proposed the idea of ​​conductive spots. For example, patent CN 109023333 B gives a height difference between the two phases of a magnesium alloy by pickling pretreatment, and uses the second phase of the alloy as a conductive spot. However, the film thickness is only 200nm, and the application of alloys is limited. It is not applicable to alloys with unclear second phases or pure magnesium. Moreover, the conductivity depends on pickling pretreatment, and the process is complicated, so it is not universal.

[0006] Therefore, it is particularly important to propose a theoretical guide for the design of film-forming solutions for the screening of film-forming materials for conductive and corrosion-resistant conversion films, which can not only reduce the cost of trial and error, but also efficiently prepare a film layer with the required performance in one step. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a method for determining a conductive corrosion-resistant conversion film-forming liquid, which can reduce the trial-and-error cost and simply and efficiently prepare a conductive corrosion-resistant magnesium alloy conversion film.

[0008] In order to solve the above technical problems, the present invention provides a method for determining a conductive corrosion-resistant conversion film forming solution, comprising the following steps:

[0009] According to the energy band of transition metal oxides, salts capable of producing oxides of Mn, V, Mo, Cr and Co are selected as alternative oxidants in the film-forming solution;

[0010] According to the electrode reaction and standard potential of the oxidant, the acidity and alkalinity of the film-forming material solution and environmental factors, salts that can produce oxides of Mn, V and Mo are selected as the alternative oxidants in the film-forming solution;

[0011] According to the precipitation equilibrium phase diagram of transition metal oxides and the precipitation equilibrium phase diagram of monohydrogen phosphate, salts that can produce oxides of Mo, Mn and V can be used as alternative oxidants in the film-forming solution;

[0012] According to the film-forming cation Ca in the film-forming substance 2+ Excluding molybdate, potassium permanganate and ammonium metavanadate were selected as oxidants in the film-forming solution;

[0013] A solution including 0.20-0.24 mol / L calcium nitrate, 0.20-0.24 mol / L ammonium dihydrogen phosphate, 0.05-0.2 mol / L potassium permanganate, and 0.01-0.03 mol / L ammonium metavanadate was determined as the membrane-forming solution.

[0014] Furthermore, the determined film-forming solution is used to prepare a conductive and corrosion-resistant magnesium alloy conversion film, comprising the following steps:

[0015] preparing magnesium alloy samples and performing surface treatment on the magnesium alloy samples;

[0016] Prepare a film-forming solution including 0.20-0.24 mol / L calcium nitrate, 0.20-0.24 mol / L ammonium dihydrogen phosphate, 0.05-0.2 mol / L potassium permanganate, and 0.01-0.03 mol / L ammonium metavanadate;

[0017] The pH of the membrane-forming solution is adjusted to 2-3 with phosphoric acid, and then the membrane-forming solution is subjected to a conversion treatment at a temperature of 60-85° C. for 5-15 minutes;

[0018] The converted film-forming liquid is placed in a water bath at 60°C-85°C for heating;

[0019] The surface treated magnesium alloy sample is placed in the heated conversion solution to form a film for 5-15 minutes;

[0020] The magnesium alloy samples after film formation were taken out, rinsed and dried before characterization.

[0021] Furthermore, the magnesium alloy samples include magnesium alloy samples cut into 40 mm×40 mm×5 mm, 5 mm×10 mm×12 mm and 25 mm×25 mm×5 mm by wire cutting.

[0022] Furthermore, the film forming temperature of the magnesium alloy sample in the conversion solution is 60°C-85°C.

[0023] Preferably, the film-forming temperature of the magnesium alloy sample in the conversion solution is 65°C.

[0024] The present invention provides a method for determining a conductive corrosion-resistant conversion film forming liquid. The transition metal oxide required for film formation is screened by calculating the transition metal oxide energy band, the oxidant reaction electrode potential, the deposition equilibrium phase diagram of the transition metal oxide, and the precipitation equilibrium phase diagram of the monohydrogen phosphate, and the oxidant that should be added to the conversion film forming liquid is determined, so that a part of the oxidant generates a transition metal oxide during the film forming process, and a part is doped in the phosphate lattice to reduce its energy band, thereby improving the conductivity of the non-conductive substance, thereby reducing the contact resistance of the film layer without reducing the corrosion resistance of the film layer, and improving the conductivity of the film layer. This can not only reduce the trial and error cost in the experiment, but also simply and efficiently prepare a conductive corrosion-resistant conversion film on the surface of the magnesium alloy. At the same time, the method for determining a conductive corrosion-resistant conversion film forming liquid provided by the present invention can be applied to all magnesium alloys and has universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A flow chart of a method for determining a conductive corrosion-resistant conversion film forming solution provided by an embodiment of the present invention;

[0026] Figure 2 A precipitation equilibrium phase diagram of transition metal oxides in a method for determining a conductive corrosion-resistant conversion film-forming solution provided by an embodiment of the present invention;

[0027] Figure 3 A precipitation equilibrium phase diagram of monohydrogen phosphate in a method for determining a conductive corrosion-resistant conversion film forming solution provided by an embodiment of the present invention;

[0028] Figure 4 An energy band diagram of CaHPO4 in a method for determining a conductive corrosion-resistant conversion film forming solution provided by an embodiment of the present invention;

[0029] Figure 5 An energy band diagram of CaHPO4 doped with Mn in a method for determining a conductive corrosion-resistant conversion film forming solution provided by an embodiment of the present invention;

[0030] Figure 6 The surface morphology of the magnesium alloy film layer obtained in Comparative Example 2 and Example 1 provided by the present invention, wherein a) Comparative Example 2; b) Example 1;

[0031] Figure 7 The cross-sectional morphology of the magnesium alloy film layer obtained in Comparative Example 2 and Example 1 provided by the present invention, wherein a) Comparative Example 2; b) Example 1;

[0032] Figure 8 This is an XPS analysis chart of the magnesium alloy film layer obtained in Comparative Example 2 provided by the present invention;

[0033] Fig. 9 This is an XPS analysis chart of the magnesium alloy film layer obtained in Example 1 provided by the present invention;

[0034] Fig.10 It is a hydrogen evolution curve of the magnesium alloy film layer of Comparative Example 1, Comparative Example 2 and Example 1 provided by the present invention in a 3.5% NaCl solution;

[0035] Fig.11 The macroscopic corrosion morphologies of the magnesium alloy film layers of Comparative Example 1, Comparative Example 2 and Example 1 provided in the present invention after 24h, 48h and 120h of neutral salt spray test respectively. DETAILED DESCRIPTION

[0036] See also Figure 1 , a method for determining a conductive corrosion-resistant conversion film forming solution provided by an embodiment of the present invention comprises the following steps:

[0037] Step 1) According to the energy band of transition metal oxides, salts capable of forming oxides of Mn, V, Mo, Cr and Co are selected as alternative oxidants in the film-forming solution.

[0038] In order to generate transition metal oxides with conductive properties during the magnesium alloy film forming process, it is necessary to add salts that can generate transition metal oxides with conductive properties as oxidants to the magnesium alloy film forming solution. In order to determine the best oxidant, the energy bands of common transition metal oxides are calculated, and the energy bands of common transition metal oxides are shown in Table 1.

[0039] Table 1

[0040] Transition Metal Oxides Energy band (eV) MnO 0.99 <![CDATA[Mn2O3]]> 0 <![CDATA[Mn3O4]]> 0 <![CDATA[MnO2]]> 0 <![CDATA[V2O3]]> 0 <![CDATA[VO2]]> 1.69 <![CDATA[MoO2]]> 0 <![CDATA[Cr2O3]]> 0 <![CDATA[CrO2]]> 0.01 ZnO 0.8 <![CDATA[Co3O4]]> 0 <![CDATA[CeO2]]> 1.86 <![CDATA[ZrO2]]> 3.13 <![CDATA[TiO2]]> 2.29 <![CDATA[In2O3]]> 0.93 FeO 1.8 <![CDATA[Ga2O3]]> 4.1 <![CDATA[Y2O3]]> 4.1 <![CDATA[La2O3]]> 3.53 <![CDATA[SnO2]]> 0.59 SnO 1.69

[0041] When the energy band is 0eV, the transition metal oxide has good electrical conductivity. Therefore, in the film forming process, salts that can form oxides of Mn, V, Mo, Cr and Co are used as alternative oxidants required for film formation. However, since the oxide of Co needs to be generated in an alkaline environment, it is not suitable for the acidic film-forming solution of the present invention, and chromates that can produce Cr oxides are restricted for use due to problems such as carcinogenicity and environmental protection, so the oxides of Cr and Co need to be excluded.

[0042] Step 2) Select salts that can generate oxides of Mn, V and Mo as alternative oxidants in the film-forming solution based on the electrode reaction and standard potential of the oxidant, the acidity and alkalinity of the film-forming solution and environmental factors.

[0043] By calculating the electrode reactions of different oxidants and their corresponding standard potentials, the electrode reactions of different oxidants and their corresponding standard potentials are shown in Table 2.

[0044] Table 2

[0045]

[0046] Since transition metal oxides have good electrical conductivity, an oxidant is added to the film-forming solution, and the standard potential is higher than that of the hydrogen evolution reaction during the film-forming process, so that electrons are obtained in priority to the hydrogen evolution reaction to generate transition metal oxides, thereby improving the electrical conductivity of the conversion film on the surface of the magnesium alloy. However, since Co oxides need to be generated in an alkaline environment, the acidic film-forming solution of the present invention is not suitable, and chromates that can produce Cr oxides are restricted from use due to problems such as carcinogenicity and environmental protection. Therefore, further screening will exclude Cr and Co oxides, and select salts that can generate Mn, V and Mo oxides as alternative oxidants in the film-forming solution.

[0047] Step 3) According to the precipitation equilibrium phase diagram of transition metal oxides and the precipitation equilibrium phase diagram of monohydrogen phosphate, oxides of Mn and V are selected as alternative oxidants in the film-forming solution.

[0048] In order to enable rapid deposition of transition metal oxides, the precipitation equilibrium phase diagrams of transition metal oxides of Mn, V, Mo, Cr and Co are calculated as follows: Figure 2 As shown. Figure 2 It can be seen that among the further screened oxides of Mn, V and Mo, the precipitation equilibrium constant of Mn oxide is the lowest, followed by Mo oxide, and finally V oxide. The oxides of the three transition metals Mn, V and Mo are all conducive to rapid deposition on the substrate. In order to improve the conductivity of the film layer in a short time, a variety of salts that can generate oxides of Mn, V and Mo can be added to the film-forming solution as oxidants to generate a variety of transition metal oxides.

[0049] In order to determine the film-forming cations in the film-forming solution, monohydrogen phosphate, which is easy to deposit, was selected. The precipitation equilibrium phase diagram of monohydrogen phosphate was obtained as shown in Figure 2 As shown. Due to the presence of oxidants in the film-forming solution, Mn, which is easily oxidized to high-valent 2+ ions, so choose Ca 2+ As a film-forming cation. 2+ In the film-forming solution, due to CaMoO4 2-It is slightly soluble in water and will make the film-forming solution ineffective. Therefore, the oxidant in the film-forming solution cannot use MoO4 that can produce Mo oxide. 2- Salts, therefore, through further screening, oxides of Mn and V were selected as alternative oxidants in the film-forming solution.

[0050] Step 4) Select Ca in the film-forming solution 2+ As film-forming cations, from the perspective of economy and cost saving, the more common and inexpensive potassium permanganate and ammonium metavanadate are selected as oxidants in the film-forming solution.

[0051] Potassium permanganate and ammonium metavanadate are selected as oxidants in the film-forming solution. During the film-forming process, a part of the oxidants generates transition metal oxides, which can improve the corrosion resistance of the conversion film formed on the surface of the magnesium alloy. The metal ions of the other part of the oxidants can be doped in the phosphate lattice to reduce its energy band and improve the conductivity of the non-conductive material of the conversion film, thereby reducing the contact resistance of the film layer without reducing the corrosion resistance of the conversion film layer and improving the conductivity of the film layer.

[0052] Step 5) After the oxidant in the film-forming solution is selected, a solution including 0.20-0.24 mol / L calcium nitrate, 0.20-0.24 mol / L ammonium dihydrogen phosphate, 0.05-0.2 mol / L potassium permanganate, and 0.01-0.03 mol / L ammonium metavanadate is determined as the film-forming solution.

[0053] When magnesium alloy is added to the film-forming solution, the reactions occurring during the film-forming process are specifically shown in reactions 1-7.

[0054] Mg-2e→Mg 2+ (1)

[0055]

[0056] When the magnesium alloy enters the acidic film-forming solution, magnesium dissolves as shown in reaction (1), and then the permanganate and metavanadate gain electrons and react with the H + ions react as shown in reactions (3)-(6). + The consumed dihydrogen phosphate ions are ionized to form monohydrogen phosphate ions, as shown in reaction (7). Subsequently, the calcium ions react with the monohydrogen phosphate to form a deposition reaction, as shown in reaction (8).

[0057] In order to ensure that transition metal ions can be doped into the CaHPO4 lattice, the radius of the transition metal ions must be smaller than that of Ca 2+ The ionic radius of several transition metal ions is shown in Table 3.

[0058] Table 3

[0059] Transition metal ions radius <![CDATA[Mn 7+ ]]> 0.25 <![CDATA[V 5+ ]]> 0.36 <![CDATA[Mn 2+ ]]> 0.72 <![CDATA[Ca 2+ ]]> 1.00

[0060] It can be seen from Table 3 that in the process of film-forming reaction of magnesium alloy in film-forming solution, the Mn formed in reaction (2) 2+ Since the radius is smaller than Ca 2+ It can be doped into the crystal lattice of CaHPO4. According to the first-principle Castep module, the energy band diagram of the oxidant in the film-forming solution is calculated. During the film-forming process, Mn will be doped into the crystal lattice of CaHPO4, causing its energy band to decrease.

[0061] See also Figure 4 It can be seen that the energy band of CaHPO4 is 5.48eV, indicating that CaHPO4 is an insulating material. Figure 5 It can be seen that when CaHPO4 is doped with Mn, impurity energy levels appear and the impurity energy levels cross the Fermi surface, indicating that the conductivity of CaHPO4 is improved, which is also an important reason for improving the conductivity of the conversion film.

[0062] Among them, the present invention provides a method for determining a conductive corrosion-resistant conversion film forming solution, wherein the determined film forming solution is used to prepare a conductive corrosion-resistant magnesium alloy conversion film, comprising the following steps:

[0063] (1) Prepare magnesium alloy samples and perform surface treatment on the magnesium alloy samples.

[0064] The magnesium alloy samples include magnesium alloy samples cut into 40 mm×40 mm×5 mm, 5 mm×10 mm×12 mm and 25 mm×25 mm×5 mm by wire cutting.

[0065] Among them, the 40mm×40mm×5mm magnesium alloy sample is used to characterize the conductive properties of the film layer after film formation, and the 5mm×10mm×12mm and 25mm×25mm×5mm magnesium alloy samples are used for morphology and corrosion resistance test characterization.

[0066] The surface treatment of the magnesium alloy sample is to polish the magnesium alloy sample with 600#, 1000#, and 12000# silica sandpaper in sequence, and then rinse with alcohol and blow dry for standby use.

[0067] (2) Prepare a film-forming solution including 0.20-0.24 mol / L calcium nitrate, 0.20-0.24 mol / L ammonium dihydrogen phosphate, 0.05-0.2 mol / L potassium permanganate, and 0.01-0.03 mol / L ammonium metavanadate.

[0068] (3) The pH of the membrane-forming solution is adjusted to 2-3 with phosphoric acid, and then the solution is subjected to a conversion treatment at a temperature of 60-85° C. for 5-15 minutes.

[0069] (4) The converted film-forming liquid is placed in a water bath at 60°C-85°C for heating.

[0070] (5) The surface-treated magnesium alloy sample is placed in the heated conversion solution to form a film for 5-15 minutes.

[0071] (6) The magnesium alloy samples after film formation are taken out, rinsed and dried before characterization.

[0072] Among them, the film forming temperature of the magnesium alloy sample in the conversion solution is 60℃-85℃.

[0073] As a specific embodiment of the present invention, the film forming temperature of the magnesium alloy sample in the conversion solution is preferably 65°C.

[0074] The following is a specific description of the method for determining the conductive corrosion-resistant conversion film forming solution provided by the present invention by using comparative examples and embodiments to use the film-forming solution determined by the present invention to prepare a conductive corrosion-resistant magnesium alloy conversion film.

[0075] Comparative Example 1

[0076] In this comparative example, no conversion treatment was performed, and the magnesium alloy matrix was directly prepared, and then the magnesium alloy matrix was characterized.

[0077] Preparation of magnesium alloy matrix

[0078] (1) The magnesium alloy was cut into 40 mm × 40 mm × 5 mm sizes by wire cutting for characterizing the conductivity of the film layer, 5 mm × 10 mm × 12 mm, and 25 mm × 25 mm × 5 mm sizes for morphology and corrosion resistance testing.

[0079] (2) Grind the specimens with 600#, 1000#, and 12000# silica sandpaper, rinse with alcohol, and blow dry.

[0080] The contact resistance of the surface of the magnesium alloy substrate obtained in Comparative Example 1 is measured and is shown in Table 5.

[0081] Comparative Example 2

[0082] The film-forming solution of this comparative example does not contain an oxidant capable of producing transition metal oxides, that is, there is no transition metal oxide in the conversion film formed on the surface of the magnesium alloy.

[0083] The method for preparing a transition metal oxide-free conversion film on the surface of a magnesium alloy substrate comprises the following steps.

[0084] (1) The magnesium alloy was cut into 40 mm × 40 mm × 5 mm sizes by wire cutting for characterizing the conductivity of the film layer, 5 mm × 10 mm × 12 mm, and 25 mm × 25 mm × 5 mm sizes for morphology and corrosion resistance testing.

[0085] (2) Grind the specimens with 600#, 1000#, and 12000# silica sandpaper, rinse with alcohol, and blow dry.

[0086] (3) Chemical conversion treatment: Dissolve 0.1-0.2 mol of calcium nitrate and 0.1-0.2 mol of ammonium dihydrogen phosphate in 1 L of water, adjust the pH to about 2-3 with phosphoric acid, and perform the conversion treatment at a temperature of 60-85°C for 10 min.

[0087] (4) Place the above solution in a water bath at 60℃-85℃.

[0088] (5) The magnesium alloy is placed in the above-mentioned heated conversion coating solution and the film is formed for 10 minutes.

[0089] (6) Take out the sample, rinse it with deionized water, and dry it in air. Perform subsequent characterization after 24 hours.

[0090] Among them, the film forming temperature is preferably 60°C-85°C, more preferably 65°C.

[0091] The contact resistance of the surface film layer of the magnesium alloy substrate obtained in Comparative Example 2 is measured and is shown in Table 5.

[0092] The surface morphology of the film layer after film formation on the magnesium alloy surface of Comparative Example 2 is as follows Figure 6 As shown, the cross-sectional morphology of the film layer after film formation on the surface of the magnesium alloy in Comparative Example 2 is as follows Figure 7 shown.

[0093] XPS analysis of the phase composition of the film layer of this comparative example 2 was performed, and the obtained XPS analysis graph is as follows: Figure 8 As shown. Figure 8 It can be seen that after carbon peak correction, the component in Comparative Example 2 is the main component of the film layer.

[0094] Example 1

[0095] The film-forming liquid of this embodiment contains an oxidant that can produce transition metal oxides, that is, the conversion film formed on the surface of the magnesium alloy contains transition metal oxides, and the formed conversion film is conductive and corrosion-resistant.

[0096] The preparation method of forming a conductive corrosion-resistant conversion film on the surface of a magnesium alloy comprises the following steps.

[0097] (1) The magnesium alloy was cut into 40 mm × 40 mm × 5 mm sizes by wire cutting for characterizing the conductivity of the film layer, 5 mm × 10 mm × 12 mm, and 25 mm × 25 mm × 5 mm sizes for morphology and corrosion resistance testing.

[0098] (2) Grind the specimens with 600#, 1000#, and 12000# silica sandpaper, rinse with alcohol, and blow dry.

[0099] (3) Chemical conversion treatment: 0.1-0.2 mol of calcium nitrate and 0.1-0.2 mol of ammonium dihydrogen phosphate are dissolved in 1 L of water, and then 0.01-0.1 mol of potassium permanganate and 0.005-0.01 mol of ammonium metavanadate are added. The pH is adjusted to about 2-3 with phosphoric acid, and the conversion treatment is carried out at a temperature of 60-85°C for 10 min.

[0100] (4) Place the above solution in a water bath at 60℃-85℃.

[0101] (5) The magnesium alloy is placed in the above-mentioned heated conversion coating solution and the film is formed for 10 minutes.

[0102] (6) Take out the sample, rinse it with deionized water, and dry it in air. Perform subsequent characterization after 24 hours.

[0103] Among them, the film forming temperature is preferably 60°C-85°C, more preferably 65°C.

[0104] The contact resistance of the surface film layer of the magnesium alloy substrate obtained in Example 1 was tested, and the results are shown in Table 4.

[0105] Table 4

[0106] sample Comparative Example 1 Comparative Example 2 Example 1 Contact resistance (mΩ) 1.7E-3 3.7E9 150.2

[0107] As can be seen from Table 5, the contact resistance of the film layer of Example 1 of the present invention is 150.2 mΩ. Compared with Comparative Example 1, the conductivity is worse, but still within the range of the contact resistance of the conductive film layer. The contact resistance of the film layer of Comparative Example 2 is 3.7E9, which can be determined to be an insulating layer without conductive properties. It can be proved that the transition metal oxide and ion doping of Example 1 of the present invention can reduce the contact resistance of the film layer and improve the conductive properties of the film layer.

[0108] The surface morphology of the film layer after film formation on the magnesium alloy surface of Example 1 is as follows Figure 6 As shown, the cross-sectional morphology of the film layer after film formation on the surface of the magnesium alloy in Example 1 is as follows Figure 7 shown.

[0109] from Figure 6 From the surface morphology, it can be seen that the film layer of comparative example 2 has a flaky structure on its surface, while the film layer of embodiment 1 of the present invention has a completely different morphology from comparative example 2. The film layer of embodiment 1 has an obvious film layer on its surface and presents a network of cracks. The existence of cracks is caused by excessive stress and dehydration in the film layer. This cracked film layer exists in the matrix phase of the magnesium alloy, and no obvious cracked film layer is found in the second phase.

[0110] from Figure 7It can be seen that the cross-sectional morphology of the film layer of comparative example 2 has an obvious film layer with a thickness of about 4 μm, but the film layer is seriously non-uniform, which will lead to an insignificant improvement in corrosion resistance. An obvious film layer can be seen in Example 2, and the film layer of Example 2 is about 1 μm. From the cross-sectional morphology of the film layer, it can be seen that Example 1 of the present invention effectively prepares a uniform film layer, thereby improving the corrosion resistance of the film layer.

[0111] XPS analysis of the phase composition of the film layer of Example 1 was performed, and the obtained XPS analysis graph is as follows: Fig. 9 shown.

[0112] from Fig. 9 It can be seen that the Ca2p orbital of Example 1 has peaks at two positions of 351.0eV and 346.5eV, indicating that the substance is CaHPO4. The P2p peak is also CaHPO4 after fitting, wherein V2p3 / 2 is V2O5 and V2O3, and Mn2p is Mn2O3 and MnO2. According to the above results, it can be explained that the main components of the film layer of Example 1 of the present invention are CaHPO4, V2O5, V2O3, Mn2O3 and MnO2. This result shows that these components are also the key to the conductivity of the film layer of Example 1 of the present invention.

[0113] In order to further evaluate the long-term corrosion resistance of the magnesium alloy and its film, the magnesium alloy substrate of Comparative Example 1 and the magnesium alloy conversion films of Comparative Example 2 and Example 1 were subjected to hydrogen evolution test and immersion test respectively. The hydrogen evolution curves of the magnesium alloy substrate of Comparative Example 1 and the magnesium alloy conversion films of Comparative Example 2 and Example 1 in 3.5wt.% NaCl solution are shown in FIG. Fig.10 The cathode reaction in the corrosion process of magnesium alloy is mainly hydrogen evolution reaction, and the hydrogen evolution rate is proportional to the corrosion rate. After chemical conversion, the amount of hydrogen evolution in magnesium alloy increases from 0.70±0.16mL·cm in comparative example 1 to -2 The value of Example 1 was reduced to 0.26±0.16 mL·cm -2 The amount of hydrogen evolution in Comparative Example 2 was 0.31±0.13 mL·cm -2 The corrosion resistance of the film is about 2 times higher than that of the comparative example 1, but lower than that of the film layer of the embodiment 1. This indicates that the conversion film of the embodiment 1 of the present invention can effectively improve the corrosion resistance of the magnesium alloy and has conductive properties.

[0114] In order to evaluate the long-term corrosion resistance of the magnesium alloy substrate of Comparative Example 1 and the magnesium alloy conversion films of Comparative Example 2 and Example 1, a neutral salt spray test was conducted. The neutral salt spray test graph obtained is as follows: Fig.11 shown.

[0115] from Fig.11It can be seen that after 24 hours of salt spray test, a small amount of corrosion has occurred on the surface of the magnesium alloy of Comparative Example 1. The corrosion points of Comparative Example 2 are significantly less than those of Comparative Example 1, indicating that the corrosion resistance of the magnesium alloy of Comparative Example 2 is improved after the conversion film is formed. However, no corrosion points appeared on the surface of Example 1 after 24 hours of salt spray test, and it still appeared golden yellow. As time went on, after 120 hours of salt spray test, the magnesium alloy of Comparative Example 1 had been severely corroded, while after 120 hours of salt spray test, there were only a small amount of corrosion points on the surface of the magnesium alloy film layer of Comparative Example 2 and Example 1, indicating that there was no obvious difference in the corrosion resistance of the magnesium alloy conversion film of Comparative Example 2 and Example 1.

[0116] It can be seen from the above experimental results that the film-forming solution determined in the embodiment of the present invention can prepare a conversion film that is both corrosion-resistant and conductive on the surface of a magnesium alloy.

[0117] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for determining a conductive corrosion-resistant conversion film forming solution, characterized in that: The steps include: According to the energy band of transition metal oxides, salts capable of producing oxides of Mn, V, Mo, Cr and Co are selected as alternative oxidants in the film-forming solution; According to the electrode reaction and standard potential of the oxidant, the acidity and alkalinity of the film-forming material solution and environmental factors, salts that can produce oxides of Mn, V and Mo are selected as the alternative oxidants in the film-forming solution; According to the precipitation equilibrium phase diagram of transition metal oxides and the precipitation equilibrium phase diagram of monohydrogen phosphate, salts that can produce oxides of Mo, Mn and V can be used as alternative oxidants in the film-forming solution; According to the film-forming cation Ca in the film-forming substance 2+ Excluding molybdate, potassium permanganate and ammonium metavanadate were selected as oxidants in the film-forming solution; A solution including 0.20-0.24 mol / L calcium nitrate, 0.20-0.24 mol / L ammonium dihydrogen phosphate, 0.05-0.2 mol / L potassium permanganate, and 0.01-0.03 mol / L ammonium metavanadate was determined as the membrane-forming solution.

2. The method for determining the conductive corrosion-resistant conversion film forming solution according to claim 1, characterized in that: The determined film-forming solution is used to prepare a conductive and corrosion-resistant magnesium alloy conversion film, comprising the following steps: preparing magnesium alloy samples and performing surface treatment on the magnesium alloy samples; Prepare a film-forming solution including 0.20-0.24 mol / L calcium nitrate, 0.20-0.24 mol / L ammonium dihydrogen phosphate, 0.05-0.2 mol / L potassium permanganate, and 0.01-0.03 mol / L ammonium metavanadate; The pH of the membrane-forming solution is adjusted to 2-3 with phosphoric acid, and then the membrane-forming solution is subjected to a conversion treatment at a temperature of 60-85° C. for 5-15 minutes; The converted film-forming liquid is placed in a water bath at 60°C-85°C for heating; The surface treated magnesium alloy sample is placed in the heated conversion solution to form a film for 5-15 minutes; The magnesium alloy samples after film formation were taken out, rinsed and dried before characterization.

3. The method for determining the conductive corrosion-resistant conversion film forming solution according to claim 2, characterized in that: The magnesium alloy samples include magnesium alloy samples cut into 40 mm×40 mm×5 mm, 5 mm×10 mm×12 mm, and 25 mm×25 mm×5 mm by wire cutting.

4. The method for determining the conductive corrosion-resistant conversion film forming solution according to claim 2, characterized in that: The film forming temperature of the magnesium alloy sample in the conversion solution is 60°C-85°C.

5. The method for determining the conductive corrosion-resistant conversion film forming solution according to claim 4, characterized in that: The film-forming temperature of the magnesium alloy sample in the conversion solution is 65°C.

Citation Information

Patent Citations

  • Preparation process of humid heat resistant, conductive and corrosion resistant chemical conversion film on magnesium alloy

    CN109023333B